Noodle Waste As Substitute For Yellow Corn in Broiler Diet and Its Effect on Carcass Quality (Jurnal Ilmu dan Teknologi Hasil Ternak, 2010)
Experiment aimed to investigate the effect of noodle waste as corn substitute in broiler diet on carcass quality including carcass weight, carcass percentage, abdominal fat percentage, breast meat depositition and cholesterol concentration. The materials used for this experiment were 100 one-day-old Lohmann broiler chicks. Feedstuffs used consisted of concentrate, rice polishing and yellow corn formulated to meet nutrient requirements during starter and finisher periods and given ad libitum. This experiment was arranged in Completely Randomized Design in five replications with five chicks each. The treatments were 0 % noodle waste in diet (P0), 10 % noodle waste in diet (P1), 20 % noodle waste in diet (P2) and 30 % noodle waste in diet, respectively.The variables measured were carcass weight (g/bird), carcass percentage (%), abdominal fat pad percentage (%), deposition of breast meat percentage (%) and meat cholesterol (mg/100g). The results showed that carcass weight and deposition of breast meat percentage were significantly influenced (P<0.01) by substitution of corn with noodle waste in broiler diet. However carcass percentage, abdominal fat pad percentage, deposition of breast meat percentage and meat cholesterol were not significantly (P>0.05) affected by the treatments. The best result was achieved by 20% noodle waste (P2) in diet. The conclusion of this experiment is that utilization of noodle waste as corn substitute in broiler diet is up to 20 % (33.33 % replacing corn). Keywords: noodle waste, diet, carcass quality, broiler